The psychological and social risks of the Internet for adolescents - BELAKHDAR, Mohamed (Social Sciences Journal)
The Internet is a visitor without introductions and as positive as it may be, in the event of a lack of censorship, it may lead to the effects of what is described as dangerous and destructive, so the countries are trying, and in order to preserve their generations, especially children and adolescents, to prevent the leakage of prohibited sites into their local networks, by means Advanced, however, information crime is progressing faster than means of protection and prevention, and accordingly it is the duty of the individual and society to make the Internet a network with a positive aspect in people’s lives, as this is the responsibility of society.